ANALISA WAKTU MERAH SEMUA (ALL RED) DIPERSIMPANGAN JALAN SETIABUDI DAN JALAN NGUMBAN SURBAKTI - Ida Deliyarti Agustina (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
The Setiabudi–Ngumban Surbakti intersection is a high-traffic area in Medan City, frequently experiencing traffic conflicts due to the high speeds of approaching vehicles, the diversity of vehicle types, and drivers frequently exceeding the stop line at the end of the yellow phase. This situation increases the risk of side collisions, especially when vehicles remain in the conflict zone after the signal changes phase. This study aims to determine the optimal all-red time to ensure the intersection is safely cleared before the next phase is signaled green. The calculation method takes into account the intersection's geometric characteristics, the conflict zone distance (D), the length of approaching vehicles (Lav), the potential presence of large vehicles within the intersection area (Lev), the speed of approaching traffic (Vav), and the additional safety buffer time (tsafe). The analysis results show that the maximum value between the length of vehicles remaining within the intersection and the conflict zone distance plus the length of approaching vehicles is dominated by large vehicles with a length of 32 meters. With an average approaching traffic speed of 50 km/h, the clearing time was 2.3 seconds, and after adding a 0.5-second safety buffer, the recommended all-red time is approximately 3 seconds. These results indicate that the all-red time setting at the Setiabudi–Ngumban Surbakti intersection needs to consider the characteristics of Medan's traffic, which is characterized by a mix of heavy vehicles, relatively high approaching speeds, and varying levels of driver compliance.